COVID-19, sustainable development challenges of Latin America and the Caribbean, and the potential engines for an SDGs-based recovery. (8th April 2021) - Gonzalez-Perez, Maria Alejandra; Mohieldin, Mahmoud; Hult, G. Tomas M.; Velez-Ocampo, Juan
Abstract : Purpose: The purpose of this study is to examine the impact of COVID-19 on the Latin America and the Caribbean (LAC) region and to discuss imperative engines for potential regional recovery. Design/methodology/approach: This study conceptually discusses the effects of COVID-19 on the LAC region and highlights potential areas for recovery. Findings: The LAC region have a history of facing structural development challenges – due to digital inequality, environmental degradation, erosion of democracy and financial debt – which have led to a profound discontent among people in the LAC region and this dissatisfaction has been intensified by the crises stemming from the COVID-19 pandemic. LAC region can increase its resilience and recover its path to sustainable development by consolidating impact-based regional value chains, attracting sustainability-themed foreign direct investment and nurturing structural development to facilitate LAC companies to expand into international markets ("multilatinas"). Research limitations/implications: There are some preliminary studies on the economic and social impact of COVID-19 on the LAC region, however, the strategies that emerging and developing economies might pursue to promptly recover are still a matter of discussion. The uncertainty and heterogeneity of the developing and emerging economies and the multidimensional needed actions require local adaptations and adjustments. Originality/value: The LAC COVID-19 crisis recovery requires shared responsibility, global solidarity, urgent and immediate cooperation and structural transformations to enable deeper regional integration. This integration should focus on impact-based value chains to be resiliently adaptable to changing global realities and arduous local contexts. This paper provides integrative avenues for potential regional recovery within the region. Abstract : Objetivo: el propósito de este manuscrito es examinar el impacto de COVID-19 en la región de Latinoamérica y el Caribe (LAC) y discutir los motores imperativos para una posible recuperación regional. Metodología: Este estudio analiza conceptualmente los efectos del COVID-19 en la región de LAC y destaca áreas potenciales de recuperación. Resultados: la región de LAC tiene un historial de enfrentar desafíos de desarrollo estructural debido a la desigualdad digital, la degradación ambiental, la erosión de la democracia y la deuda financiera, que han llevado a un profundo descontento entre las personas de LAC, y esta insatisfacción se ha visto intensificada por las crisis derivadas de la pandemia de COVID-19. La región de LAC puede aumentar su resiliencia y recuperar su camino hacia el desarrollo sostenible mediante la consolidación de más cortas cadenas de valor regionales basadas en el impacto, la atracción de Inversión Extranjera Directa (IED) con temas de sostenibilidad y el fomento del desarrollo estructural para facilitar la expansión de las empresas de LAC en los mercados internacionales ("multilatinas"). Originalidad/valor: la recuperación de la crisis del COVID-19 en LAC requiere de responsabilidad compartida, solidaridad global, cooperación urgente e inmediata y transformaciones estructurales que permitan una integración regional más profunda. Esta integración debe centrarse en las más cortas cadenas de valor basadas en el impacto para que se adapten con resiliencia a las cambiantes realidades globales y los arduos contextos locales. Este manuscrito proporciona vías integradoras para una posible recuperación regional dentro de la región. Implicaciones/limitaciones de la investigación: Existen algunos estudios preliminares sobre el impacto económico y social del COVID-19 en la región de LAC, sin embargo, las estrategias que las economías emergentes y en desarrollo podrían seguir para recuperarse rápidamente son aún un tema de discusión. La incertidumbre y heterogeneidad de las economías en desarrollo y emergentes y las acciones multidimensionales necesarias requieren adaptaciones y ajustes locales. Abstract : Objetivo: o objetivo deste manuscrito é examinar o impacto do COVID-19 na região da América Latina e do Caribe e discutir mecanismos imperativos para uma potencial recuperação regional. Metodologia: este estudo discute conceitualmente os efeitos do COVID-19 na região da América Latina e do Caribe e destaca áreas potenciais para recuperação. Resultados: a região da América Latina e do Caribe (LAC) tem um histórico de desafios estruturais de desenvolvimento – devido à desigualdade digital, degradação ambiental, erosão da democracia e dívida financeira – que levaram a um profundo descontentamento entre as pessoas na região da LAC, e essa insatisfação foi intensificada pelas crises decorrentes da pandemia COVID-19. A região da LAC pode aumentar sua resiliência e recuperar seu caminho para o desenvolvimento sustentável consolidando cadeias de valor regionais com impacto econômico e social, atraindo Investimento Estrangeiro Direto (IED) com foco em sustentabilidade e fomentando o desenvolvimento estrutural para facilitar a expansão das empresas da LAC para mercados internacionais ("multilatinas") Originalidade: a recuperação da crise LAC COVID-19 requer responsabilidade compartilhada, solidariedade global, cooperação urgente e imediata e transformações estruturais para permitir uma integração regional mais profunda. Essa integração deve se concentrar em cadeias de valor baseadas em impacto para serem resilientemente adaptáveis às mudanças nas realidades globais e nos contextos locais árduos. Este manuscrito oferece caminhos integrativos para uma potencial recuperação regional. Implicações/limitações da pesquisa: existem alguns estudos preliminares sobre o impacto econômico e social do COVID-19 na região da LAC; no entanto, as estratégias que as economias emergentes e em desenvolvimento podem seguir para se recuperar prontamente ainda estão em discussão. A incerteza e a heterogeneidade das economias em desenvolvimento e emergentes, assim como as ações multidimensionais necessárias requerem adaptações e ajustes locais.